Pengaruh Perlakuan Panas Setelah Brazing Dengan Menggunakan Metode Taguchi - Ibnu Muzaki; Lobes Herdiman; Eko Pujiyanto (Industrial Engineering Study Program, Faculty of Engineering, Universitas Sebelas Maret, 2005)
Experiment use Taguchi method, with quality characteristic is shear strength at brazing joint based on standard examination of AWS C3.2M/C3.2:2001, while anticipated factor can improve shear strength is temperature, time held up and refrigeration method at heat treatment process. Data processing use two analysis to determine optimal level setting, consist of analysis of mean and analysis of signal to noise ratio, then conducted confirmation experiment to test value of factor level setting predicted at optimal condition.